Student nurses' perceptions of the development of interpersonal relationships - P.W. Solombela; V.J. Ehlers (AOSIS, 2002)
This survey attempted to investigate: • whether significant differences existed between the first and fourth year students' perceptions about the espousal of positive interpersonal relationships • student nurses' perceived role of tutors, preceptors and professional nurses in fostering the development of students nurses' positive interpersonal relationships • student nurses' espousal of positive interpersonal relationships with colleagues, patients, friends and relatives of patients .